KOMUNIKASI ORGANISASI DALAM MENDORONG KINERJA KARYAWAN PADA DIVISI CORPORATE AND GOVERNMENT TRANS TV - Ratu Chiandita; Suparman Suparman; Amiruddin Saleh; Rici Tri Harpin; Nabhila Manisya; Khalila Zahra Maharani; Anggi Widia; Maharani Azzahra (Communicative : Jurnal Dakwah dan Komunikasi, 2024)
This study aims to determine the role of organizational communication in improving employee performance in the Corporate and Government Division of Trans TV. The main problem discussed in this research is how the form of internal communication applied by the division and the role of communication in encouraging employee performance. Using a descriptive qualitative approach through a case study method, this research used in-depth interviews with a number of employees and secondary data analysis. The results show that organizational communication consisting of vertical, horizontal, and diagonal communication has been implemented by Trans TV's Corporate and Government Division. The vertical communication applied uses The Equalitarian Style approach. Horizontal communication that is applied plays a role in facilitating coordination between coworkers, supported by strategic workspaces, while diagonal communication accelerates cross-division decision making. This form of communication creates a comfortable work environment, strengthens relationships, and encourages employee performance and can reduce conflict, increase a sense of community, and maintain employee motivation. It can be concluded that organizational communication in the Corporate and Government Division of Trans TV plays a role in encouraging employee performance.